Supply Chain Performance Measurement Framework For State-Owned Entities in South Africa - Intaher Marcus Ambe; Rebecca Setino; Ellsworth Chouncey Jonathan (International Journal of Supply Chain Management, 2022)
State-Owned Entities in South Africa remain the major contributor toward socio-economic objectives, the bottom line, quality, value creation and cost savings. Although the National Treasury's Office of the Chief Procurement Officer monitors and evaluates supply chain performance, there is inefficient guidance on executing supply chain performance measurements in state-owned entities. Therefore, this paper aims to suggest a supply chain performance framework suitable for State-Owned Entities in South Africa. The manuscript employs a theoretical literature review on supply chain performance measurement systems and associated metrics. Further study using mixed methods or qualitative research is recommended to understand better the connection between supply chain strategy, SCM regulatory frameworks, SCM practices, and SCM effectiveness. The paper presents a framework that adequately implements supply chain performance measurement in state-owned entities. The study's main limitation was that it was restricted to SOEs registered with the SOEPF; more extraordinary samples from various SOEs would have been ideal. It is recommended that supply chain managers in state-owned entities carefully select supply chain performance measures.